2002
DOI: 10.1097/00004728-200207000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Affecting Bolus Geometry in CTA: A Review

Abstract: CT angiography (CTA) is based on acquisition of data during the arterial phase of contrast material passage. CTA needs timing of the contrast bolus, which should be based on accurate knowledge of bolus geometry. Experimental and human studies on bolus geometry and bolus timing in CTA were reviewed. Important parameters of bolus geometry and methods of bolus timing (test bolus and bolus tracking) are described. Recommendations are given for an optimal CTA protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(116 citation statements)
references
References 50 publications
0
112
1
3
Order By: Relevance
“…A study of coronary artery CT has shown enhancement to be more homogeneous when bolus tracking is used compared with the test bolus method. 15 We, therefore, use bolus tracking for CT scanning of head and neck vessels in routine clinical examinations. Test bolus administration is used for perfusion imaging: The scan for determining arrival of the test bolus is positioned intracranially, precluding relevant exposure of the most radiation-sensitive head and neck organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of coronary artery CT has shown enhancement to be more homogeneous when bolus tracking is used compared with the test bolus method. 15 We, therefore, use bolus tracking for CT scanning of head and neck vessels in routine clinical examinations. Test bolus administration is used for perfusion imaging: The scan for determining arrival of the test bolus is positioned intracranially, precluding relevant exposure of the most radiation-sensitive head and neck organs.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation dose measurements were performed on a 64-detector row CT scanner (Aquilion 64; Toshiba Medical Systems, Tokyo, Japan) and on a 320-detector row scanner (Aquilion ONE, Toshiba Medical Systems) by using standardized protocols for comprehensive stroke imaging, 15 which include noncontrast head CT scans, perfusion imaging, and scanning of the cervicocranial vessels starting at the aortic arch. For a 64-detector row scanner, the recommended protocol consists of a noncontrast incremental CCT; a CTP, which has a length of 32 mm on the scanner we used; and CTA in the helical mode extending from the origin of the cervicocranial arteries from the aortic arch to the vertex (34 cm).…”
Section: Protocolsmentioning
confidence: 99%
“…Most previous work looking at the effects of variations of these parameters on bolus geometry has been done to try to optimize arterial opacification following an intravenous injection of contrast medium so as to improve the image quality of intravenous digital subtraction angiography (DSA), MR angiography, and CT angiography (CTA). [4][5][6][7] Although there is very likely a close relationship between the effects of these manipulations on an intra-arterial injection and an intravenous injection in the same subject, to our knowledge, this has not been previously studied.…”
mentioning
confidence: 91%
“…The attenuation of coronary vessel is influenced by the individual patients weight, height (expressed by body mass index (BMI) and body surface area (BSA)) and cardiac output [8][9][10][11][12][13], as well as by technical factors related to the type and iodine concentration of the CM [7], the technique for bolus timing [6], the injection volume and rate [14], and tube voltage [15]. Previous CTCA protocols [2,[16][17][18] did not adapt to patients individual body mass or cardiac output.…”
Section: Introductionmentioning
confidence: 99%